Restructuring The Minimum Wage System to Ensure Worker Welfare in The Dynamics of The Modern Economy - Ilyas Panji Alam; Lucky Ferdiles (Al-Makki Publisher, 2026)
This study aims to examine and reconstruct the minimum wage system in Indonesia to realize justice and worker welfare. The method used is normative juridical research with statutory and conceptual approaches, through an analysis of Law Number 13 of 2003 concerning Manpower, as amended by Law Number 6 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation into Law and its implementing regulations. The results of the study show that the minimum wage system has been normatively regulated to ensure a decent livelihood; however, in its implementation, there are still normative disharmony, a paradigm shift toward a macroeconomic approach, and various empirical problems, such as wage disparities between regions, weak supervision, and low worker participation. These conditions create a gap between das Sollen and das Sein, so the objective of legal protection has not been achieved optimally. This study concludes that the reconstruction of the minimum wage system is necessary through strengthening the aspect of decent living needs in the wage formula, increasing worker participation, and reinforcing supervision and law enforcement to create a fair, adaptive, and welfare-oriented wage system